Analysis of the Influence of Poverty, Human Development Index, and Population on Income Inequality in North Sumatra 2018-2022 - Simbolon, Cinta Marito; Nisa, Fadila; Pinem, Haifa Azalia; Sinaga, Darwin Eros; Tobing, Roy Kristanto Lumban; Hidayat, Nasrullah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to find out how much influence poverty, the human development index, and population have on income inequality in North Sumatra for the 2018-2022 period. This research uses quantitative methods with descriptive analysis. The data used in this research is secondary data sourced from the North Sumatra Central Statistics Agency (BPS) for 4 years from 2018-2022. The data analysis technique uses Fixed Effects based on the results of the Chow test and Hausman test. The results of this research show that (1) the independent variables, namely poverty, HDI, and population have a significant effect on inequality in North Sumatra province, (2) poverty has a negative effect but does not have a significant effect on income inequality in North Sumatra province. North Sumatra, (3) the HDI variable has a negative and significant effect on income inequality in North Sumatra. and (4) the Population variable has a positive and significant effect on income inequality in North Sumatra.